Agonists of toll-like receptor (TLR)2 and TLR4 are unable to modulate platelet activation by adenosine diphosphate and platelet activating factor - Ward, Jon R; Bingle, Lynne; Judge, Heather M; Brown, Simon B; Storey, Robert F; Whyte, Moira K B; Dower, Steven K; Buttle, David J; Sabroe, Ian (Thrombosis and haemostasis, 2005)
Inappropriate platelet activation is a feature of acute and chronic diseases such as disseminated intravascular coagulation (DIC) and atherosclerosis. Since proinflammatory microbial-derived agonists can be involved in the pathogenesis of these diseases, we examined the potential role of TLR4 (mediating responses to LPS) and TLR2 (which responds to bacterial lipopeptides) in platelet activation. Our data suggested low-level expression of TLR2 and TLR4 on platelets, determined by flow cytometry, and we also observed expression of TLR4 on a megakaryocytic cell line by both flow cytometry and immunohistochemistry. Stimulation of the platelets with the TLR4 agonist LPS, and the synthetic TLR2 agonist Pam3CSK4, resulted in no platelet aggregation, no increase in CD62P surface expression and no increase in the cytosolic concentration of Ca2+. The TLR agonists were also unable to directly activate platelets primed with epinephrine, or pretreated with a low concentration of ADP or PAF. Pretreatment of platelets with LPS or Pam3CSK4 also failed to modulate the platelet response to submaximal concentrations of the classical platelet agonists ADP and PAF. We conclude that the TLR agonists LPS and Pam3CSK4 have no direct effect on platelet activation and that platelet TLRs may be a remnant from megakaryocytes. TLR2 and TLR4 agonists are thought to have a significant role in diseases such as atherosclerosis and DIC, but our research suggests that this is through a mechanism other than direct platelet activation or by modification of platelet responses to other agonists.